INTERACTIVE MULTIMEDIA APPLICATION TO INCREASE INTEREST AND LEARNING OUTCOME OF 4TH GRADE STUDENTS OF SDN PALERAN 05 IN MATERIAL OF PROPERTIES OF LIGHT - Lestari, Ina Fatikha Dwi; Supriadi, Bambang; Nuraini, Lailatul; Muslimin, Rianto (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
Abstract This research aims to improve the learning practices in order to increase student interest and learning outcomes through the application of interactive multimedia in the material of the properties of light. This research is a Classroom Action Research (CAR) using a two-cycle design according to Arikunto et al. The subjects of this research are the 4th grade students of SDN Paleran 05 in the academic year 2021/2022, of 9 students. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The percentage of students’ learning interest obtained from the pre-cycle questionnaire results was 53.91% (sufficient) increased to 74.58% (high) in the first cycle and 74.72% (high) in the second cycle. Meanwhile, from the observations, the pre-cycle 58.33% (sufficient) increased to 81.11% (very high) in the first cycle, then it became 86.54% (very high) in the second cycle. The data of learning outcomes find out by written test and then analyzed using N-Gain. The results showed that students’ learning outcomes increased in the first cycle by 0.48 and the second cycle by 0.31, so it can be concluded that interactive multimedia can increase students’ interest and learning outcomes. Keywords: Science; Interest; Learning Outcomes